2004
DOI: 10.1590/s0101-60832004000400007
|View full text |Cite
|
Sign up to set email alerts
|

Peculiaridades do tratamento da anorexia e da bulimia nervosa na adolescência: a experiência do PROTAD

Abstract: Os transtornos alimentares são patologias severas, tendo aspectos especiais na adolescência. Este artigo objetiva apresentar a rotina de atendimento e as abordagens empregadas em um serviço de assistência brasileiro especializado no tratamento de transtornos alimentares nessa população.Palavras-chave: Transtornos alimentares, tratamento, adolescência. AbstractThe particular aspects of eating disordes in adolescents are reviwed. This article presents the multidisciplinary approach used in this population.Keywor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
19

Year Published

2007
2007
2008
2008

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 8 publications
0
13
0
19
Order By: Relevance
“…17 NB manifests in adolescents as compulsive behavior strongly associated with personality disorders, anxiety, obsessive-compulsive disorder, depression, humor disorders, and use or dependency on substances such as alcohol and other stimulants. 3 From a psychological perspective, there is a strong relation between eating disorders, such as NB and NA, and depression. Investigating the time sequence in which comorbid disorders manifest across life is an interesting life of research that has provided important insights.…”
Section: Bulimia and Its Complicationsmentioning
confidence: 99%
See 3 more Smart Citations
“…17 NB manifests in adolescents as compulsive behavior strongly associated with personality disorders, anxiety, obsessive-compulsive disorder, depression, humor disorders, and use or dependency on substances such as alcohol and other stimulants. 3 From a psychological perspective, there is a strong relation between eating disorders, such as NB and NA, and depression. Investigating the time sequence in which comorbid disorders manifest across life is an interesting life of research that has provided important insights.…”
Section: Bulimia and Its Complicationsmentioning
confidence: 99%
“…15 Although NB usually initiates in adolescence or early adulthood, studies on NB have investigated mostly adult samples, possibly because medical help tends to be sought at this time. 3 A North-American study of eight bulimic singers that also had GERD, aged between 24 and 34 years, revealed that they complained of hoarseness, laryngeal pain, voice fatigue, phlegm, lower-pitched voice, recurring voice loss and ardor. Laryngeal findings in this group were posterior edema, posterior commissure hypertrophy, ventricular obliteration, polypoid-type degeneration and teleangiectasia.…”
Section: Voice and Bulimiamentioning
confidence: 99%
See 2 more Smart Citations
“…As intervenções nos transtornos alimentares foram abordadas por meio das experiências de equipes especializadas 79 , da clinica hospitalar 80 e de técnicas grupais 81 , psicodinâmica 82 e cognitiva 83 . Predominaram discussões teóricas baseadas em compreensões das alterações da imagem corporal 84 , da dinâmica da personalidade 78 e de conflitos familiares 85 .…”
Section: Transtornos Alimentaresunclassified